Cover Feature: Tuning Ruthenium Carbene Complexes for Selective P−H Activation through Metal‐Ligand Cooperation (Chem. Eur. J. 69/2021). Issue 69 (23rd November 2021) - Feichtner, Kai‐Stephan; Scharf, Lennart T.; Scherpf, Thorsten; Mallick, Bert; Boysen, Nils; Gessner, Viktoria H.
Abstract : P−H bond activation is an important step in many catalytic applications involving the formation of new P−C bonds. The icebreaker "RV Bond Activation", which symbolizes our carbene complexes depicted by the constellation in the sky, is able to easily break P−H bonds via the carbene linkage. The splitting of phosphines into protons and phosphide fragments (depicted as ice shards flying away) occurs even at low temperatures. More information can be found in the Full Paper by V. H. Gessner et al. (DOI: 10.1002/chem.202103151 ).